2013
DOI: 10.1115/1.4023376
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Technique to Acquire Cavity Pressure Using a Surface Strain Sensor During Injection-Compression Molding

Abstract: A new technique was proposed and experimentally verified for the cavity pressure acquisition in the injection-compression molding (ICM). The surface strain of the fixed mold half and the cavity pressure were monitored simultaneously during ICM. In the compression stage, a directly proportional relationship between the cavity pressure and mold surface strain was found and determined via the regression analysis. By taking the advantage of this relationship, the cavity pressure profile with high accuracy was indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Cavity pressure has been found to be a reliable process indicator in injection molding, for both part quality and process monitoring [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, it has been found to provide real-time detection of part and process deviation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cavity pressure has been found to be a reliable process indicator in injection molding, for both part quality and process monitoring [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, it has been found to provide real-time detection of part and process deviation.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature signal showed a reliable correlation with respect to the resin-arrival-time difference, but the pressure signal did not produce a reliable result. Guan et al [ 25 ] proposed that the mold surface strain profile could indicate the part weight or thickness and the critical time when the part surface lost contact with the cavity surface in a large area. The monitoring of the mold surface strain could serve as an interesting alternative to the direct monitoring of the cavity pressure, with respect to process and part quality control for ICM.…”
Section: Introductionmentioning
confidence: 99%
“…A previous work [24] was carried out by the authors to investigate the role of the mold surface strain playing in the process monitoring of ICM. The results implied that the peak mold surface strain quantitatively depended on the peak cavity pressure in the compression stage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, product quality can be monitored by installing sensors at different runner positions. Guan and Huang [20] used a surface strain sensor and pressure sensors installed at the cavity and surface of the mold, respectively, and found that the cavity pressure was proportional to the mold surface strain through a data-based regression method. Using this correlation, the precise cavity pressure distribution could be obtained indirectly via mold surface strain data.…”
Section: Process Optimizationmentioning
confidence: 99%